The Comparative Analysis of the Evil Issue from the Perspective of Ibn Arabî, Mullā Ṣadrā and Spinoza - Ramin Golmakani; Rasool Padashpour; Mohammad Mahdi Salami (آموزه‌‌های فلسفه اسلامي, 2020)
The question of evil is one of the most important philosophical issues that have always been raised among the religions to answer the conflict between monotheism as the origin of objects, and the existence of evil in the system of existence. On the other hand, the denouncers of God used this as a proof against the existence of God in order to oppose the religion. So the answer to the problem of evil has occupied the mind of every thinker. One of the philosophical concerns of philosophers throughout history has been to answer this question, and each has sought to solve it with its own intellectual apparatus. One of the views expressed is that evil is negative entity that philosophers have come to terms with different meanings. Ibn Arabi in theoretical mysticism and Mulla Sadra in transcendent wisdom are among those who regard evil as negative entity. As one of the Jewish philosophers, Spinoza holds that evil is a negative entity, but each has a different view of evil as negative entity. In this article, we will examine and compare the views of these thinkers and provide an analysis of each person’s ability or inability to solve the problem of evil.